Career Sustainability in AI-Driven Tourism: The Mediating Role of Career Adaptability between Grit, Resilience, and Technological Learning Support - Kusumo, Henricus Kurniawan Elang; Diena M Lemy; Tiurida Lily Anita (Politeknik Pariwisata Makassar, Indonesia, 2026)
In the rapidly evolving landscape of tourism shaped by Artificial Intelligence (AI), ensuring long-term career sustainability for future tourism professionals has become a critical concern for higher education institutions. This study aims to examine the mediating role of Career Adaptability in the relationship between three key predictors—Grit, Resilience, and Technological Learning Support (TLS)—and Career Sustainability among tourism students in Indonesia. Adopting a quantitative research approach, the study utilized Partial Least Squares Structural Equation Modeling (PLS-SEM) to analyze data from senior tourism students enrolled at various universities. The findings demonstrate that Grit, Resilience, and TLS each have a significant positive influence on Career Sustainability. Furthermore, Career Adaptability serves as a vital psychological mechanism that strengthens the connection between these predictors and sustainable career development. The study concludes that fostering adaptability enables tourism students to leverage their internal strengths and external learning resources effectively, thereby preparing them to thrive in AI-driven professional environments. The research contributes to career development literature by integrating psychological and technological dimensions within an AI-centric context, offering practical insights for educators and curriculum designers committed to producing resilient and future-ready tourism graduates.